Clinical recommendations for pain, sedation, withdrawal and delirium assessment in critically ill infants and children: an ESPNIC position statement for healthcare professionals - Harris, Julia; Ramelet, Anne-Sylvie; van Dijk, Monique; Pokorna, Pavla; Wielenga, Joke; Tume, Lyvonne; Tibboel, Dick; Ista, Erwin (Intensive care medicine, 2016)
BACKGROUND: This position statement provides clinical recommendations for the assessment of pain, level of sedation, iatrogenic withdrawal syndrome and delirium in critically ill infants and children. Admission to a neonatal or paediatric intensive care unit (NICU, PICU) exposes a child to a series of painful and stressful events. Accurate assessment of the presence of pain and non-pain-related distress (adequacy of sedation, iatrogenic withdrawal syndrome and delirium) is essential to good clinical management and to monitoring the effectiveness of interventions to relieve or prevent pain and distress in the individual patient. METHODS: A multidisciplinary group of experts was recruited from the members of the European Society of Paediatric and Neonatal Intensive Care (ESPNIC). The group formulated clinical questions regarding assessment of pain and non-pain-related distress in critically ill and nonverbal children, and searched the PubMed/Medline, CINAHL and Embase databases for studies describing the psychometric properties of assessment instruments. Furthermore, level of evidence of selected studies was assigned and recommendations were formulated, and grade or recommendations were added on the basis of the level of evidence. RESULTS: An ESPNIC position statement was drafted which provides clinical recommendations on assessment of pain (n = 5), distress and/or level of sedation (n = 4), iatrogenic withdrawal syndrome (n = 3) and delirium (n = 3). These recommendations were based on the available evidence and consensus amongst the experts and other members of ESPNIC. CONCLUSIONS: This multidisciplinary ESPNIC position statement guides professionals in the assessment and reassessment of the effectiveness of treatment interventions for pain, distress, inadequate sedation, withdrawal syndrome and delirium.
Keywords: Assessment; jednotky intenzivní péče; Intensive Care Units; Substance Withdrawal Syndrome; Sedation; Child, Preschool; Infant; Child; psychický stres; Critical Illness; Emergence Delirium; měření bolesti; dítě; delirium; Distress; Pain; psychomotorický neklid; Practice Guidelines as Topic; Pain Management; novorozenec; předškolní dítě; abstinenční syndrom; lidé; kritický stav; management bolesti; pooperační delirium; Humans; konsensus; Stress, Psychological; Infant, Newborn; kojenec; Delirium; Withdrawal syndrome; Consensus; hypnotika a sedativa; Pain Measurement; Hypnotics and Sedatives; směrnice pro lékařskou praxi jako téma; Psychomotor Agitation